Acupuncture alters the intestinal microbiota in mice with valproic acid (VPA)-induced autism-like behavior - Zirong Bai; Qingran Li; Xiaojin Qin; Jiande Chen; Meng Wang (Medicine in Microecology, 2022)
Gut microbiota influences the development of brain and behaviors in patients with autism. Acupuncture therapy reportedly alleviates the symptoms of patients with autism and can regulate the gut microbiota of patients with a disease of the central nervous system via the gut microbiota-brain axis. However, whether acupuncture therapy influences the function and composition of the gut microbiota in patients with autism remains unclear. Therefore, the present study was conducted using a valproic acid (VPA)-induced autism mouse model to investigate how acupuncture therapy influences the intestinal microbiota in terms of species diversity, composition, and function. Mice were treated with VPA to induce autism, and then divided into two groups: autism without treatment (ASD) and autism with manual acupuncture (ASD-MA). Mice in the ASD-MA group were treated with acupuncture once daily for four weeks. And behavior test was performed. Total bacterial DNA was extracted from stool samples to amplify and sequence the V3–V4 regions of 16 ​S rRNA. The alpha and beta diversity were analyzed, and changes in intestinal microbiota composition at various taxonomic levels were analyzed. The Morris water maze test results showed that the number of times the mice reached the platform was significantly higher in the ASD-MA group than in the ASD group. The results of nonmetric multidimensional scaling and principal coordinate analysis, which were used for beta diversity analyses, revealed significant differences in the microbial communities between the ASD and ASD-MA groups. The ASD-MA group mice had changed abundances of some specific microbiota, which were positively correlated with better cognitive performance. Accordingly, the gut microbiota, such as Flavonifractor, Akkermansia, Dorea, Ruminococcus, and Barnesiella, may affect cognitive function of VPA-induced autism mice after acupuncture treatment. In conclusion, the results revealed that acupuncture therapy could affect the composition of the gut microbiota in mice with VPA-induced autism-like behavior.